Diagnosing Herbicide Injury in Peanut - Sergio Morichetti; J. A. Ferrell; Pratap Devkota (EDIS)
This 9-page publication aims to provide information on peanut injury symptoms related to various herbicide modes of action and help in identifying general injury symptoms associated with certain herbicide mode of action groups. Written by S. Morichetti, J. Ferrell, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised April 2020.